Improving blood pressure control in primary care: The ImPress study. (July 2019) - Stephen, Catherine; Halcomb, Elizabeth; McInnes, Susan; Batterham, Marijka; Zwar, Nick
Abstract: Background: Hypertension is a preventable risk factor for cardiovascular disease, the leading cause of death globally. When hypertension is present with tobacco smoking, poor nutrition, physical inactivity or excessive alcohol consumption, risk of cardiovascular disease is increased. Given the prolonged engagement and ongoing relationship with patients, general practice nurses are ideally situated to actively engage with patients about optimal blood pressure control and lifestyle risk reduction. Objectives: This study will test the effectiveness of a nurse-led intervention to reduce blood pressure in adults with hypertension and high cardiovascular risk. Design: A multi-site, cluster randomised control trial where the general practice is the unit of randomisation. Methods: General Practices (n = 20) will be block randomised to the intervention or usual care group. Adults with hypertension and high cardiovascular risk will be identified through an audit of electronic medical records and invited to attend an assessment visit. Eligible consenting patients will be recruited to the study. The intervention involves three face-to-face consultations and two telephone consultations with the nurse to assess lifestyle risk and develop an action plan. An appointment with the general practitioner will optimise pharmacotherapy. The primary outcome is blood pressure, with secondary outcomes of lifestyle risk factors; smoking, nutrition, alcohol and physical activity body mass index and medication adherence. Patients will have outcome measures evaluated at 6 and 12 months. Discussion: ImPress is innovative in its proactive approach of identifying those at greatest risk of cardiovascular disease in combination with the emerging role of the general practice nurse to target care towards improved blood pressure control. If successful, findings from this trial could enhance the nursing role, improve health outcomes, inform health policy and provide an evidence base from which to transform blood pressure management in general practice. Trial Registration: This trial has been registered with the Australian and New Zealand Clinical Trials Registry as ACTRN12618000169246.